Artificial glycan-glycolipid complexes as antiviral means and effectors of microbial formulation on the base of rhizobia - Kovalenko, O.G.; Vasilev, V.M.; Adamchuk-Chala, N.I.; Tytova, L.V.; Karpenko, E.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
Artificial glycan-glycolipid complexes (GGC) formed on the base of glucan from the mycelium of basidiomicota fungi Ganoderma adspersum (Schulzer) Donk, extracellular glucouronoxylomannan of basidiomicota fungi Tremella mesenterica Ritz. Fr., mannan from Candida maltosa cells, and ramnolipid of Pseudomonas sp. PS-17 as a compound agent, and GGC fractions (liposomes and supernatant) have an inhibiting activity against virus of tabacum mosaic (VTM) of datura (Datura stramonium (L.) and tabacum (Nicotiana tabacum L.) plants up-sensitive to this virus. Under by the treatmen of soybean (Glycine max (L.) Merr.) seeds bioformulations, the plant resistance to mosaic virus infections (diseases) and the reflection of leaf light spectra, which characterized of chlorophills under field conditions are increased. By electron-microscopy investigations, the structures as type as liposoms were found out in the near-root plant zone, it can indicates on their influence to the processes of plant— rhyzospheric microoganisms interactions. Seeds bacterization by Bradyrhizobium japonicum UCM B-6018 in combination with GGC-3 preparation promotes the crop increase in field experiments.